“GREEN GROWTH” ASSESSMENT CHALLENGES IN THE BUSINESS SECTOR - Khachatryan, Nonna; Mirzoyan, Narine; Hakobjanyan, Anna (Bulletin of Yerevan University G: Economics, 2025)
Green growth assessment is considered relevant in assessing the effectiveness of sustainable organizations. However, while internationally recognized “Green growth” indices are used in the macroeconomic sphere, simultaneously green growth assessments are not yet regulated at the microeconomic level. The article explains the specifics of green growth in the business environment and presents recommendations on their accountability and measurability. In particular, it is recommended to assess the green growth generated by organizations using KPIs and implement appropriate accountability in this regard.